“The Ocean in Us”: Navigating the Blue Humanities and Diasporic Chamoru Poetry - Craig Santos Perez (Humanities, 2020)
This essay will explore the complex relationship between Pacific Islander Literature and the “Blue Humanities,” navigation traditions and canoe aesthetics, and Chamoru migration and diaspora. First, I will chart the history, theory, and praxis of Pacific voyaging traditions; the colonial history of restricting indigenous mobilities; and the decolonial acts of seafaring revitalization in the Pacific (with a specific focus on Guam). Then, I will examine the representation of seafaring and the ocean-going vessel (the canoe) as powerful symbols of Pacific migration and diasporic cultural identity in the context of what Elizabeth DeLoughrey termed, “narrative maritime legacies” (2007). Lastly, I will conduct a close-reading of the avant-garde poetry collection, A Bell Made of Stones (2013), by Chamoru writer Lehua Taitano. As I will show, Taitano writes about the ocean and navigation in order to address the history and traumas of Chamoru migration and diaspora. In terms of poetic form, I will argue that Taitano’s experimentation with typography and visual poetry embodies Chamoru outrigger design aesthetics and navigational techniques. In the end, I will show how a “Blue Humanities” approach to reading Pacific Islander literature highlights how the “New Oceania” is a profound space of Pacific migration and diasporic identity.